Health-related quality of life improves during one year of medical and surgical treatment in a European population-based inception cohort of patients with Inflammatory Bowel Disease — An ECCO-EpiCom study☆. (1st September 2014) - Burisch, J.; Weimers, P.; Pedersen, N.; Cukovic-Cavka, S.; Vucelic, B.; Kaimakliotis, I.; Duricova, D.; Bortlik, M.; Shonová, O.; Vind, I.; Avnstrøm, S.; Thorsgaard, N.; et al.
Abstract: Background & Aims: Health-related quality of life (HRQoL) is impaired in patients with Inflammatory Bowel Disease (IBD). The aim was prospectively to assess and validate the pattern of HRQoL in an unselected, population-based inception cohort of IBD patients from Eastern and Western Europe. Methods: The EpiCom inception cohort consists of 1560 IBD patients from 31 European centres covering a background population of approximately 10.1 million. Patients answered the disease specific Short Inflammatory Bowel Disease Questionnaire (SIBDQ) and generic Short Form 12 (SF-12) questionnaire at diagnosis and after one year of follow-up. Results: In total, 1079 patients were included in this study. Crohn's disease (CD) patients mean SIBDQ scores improved from 45.3 to 55.3 in Eastern Europe and from 44.9 to 53.6 in Western Europe. SIBDQ scores for ulcerative colitis (UC) patients improved from 44.9 to 57.4 and from 48.8 to 55.7, respectively. UC patients needing surgery or biologicals had lower SIBDQ scores before and after compared to the rest, while biological therapy improved SIBDQ scores in CD. CD and UC patients in both regions improved all SF-12 scores. Only Eastern European UC patients achieved SF-12 summary scores equal to or above the normal population. Conclusion: Medical and surgical treatment improved HRQoL during the first year of disease. The majority of IBD patients in both Eastern and Western Europe reported a positive perception of disease-specific but not generic HRQoL. Biological therapy improved HRQoL in CD patients, while UC patients in need of surgery or biological therapy experienced lower perceptions of HRQoL than the rest.